Fikih Perlawanan Kolonialisme Ahmad Rifa’i - Dahrul Muftadin (Jurnal Penelitian, 2017)
This paper aims to trace the stream of fiqh (principles of Islamic jurisprudence) by KH Ahmad Rifai as a form of protest against the Dutch colonialism that resulted in the suffering of the people in various regions. Through a qualitative approach by collecting data from various sources, both literature and interviews to the living witnesses, this study yields the conclusion that the resulting fiqh product is oriented towards resistance against the colonial government which is considered to be kÄfir. People who support the colonial government are labeled as ungodly, so it is illegal to be an imam (leader) of a prayer as well as to marry.